Digital literacy of educators and their acceptance of MOOC platforms in Gulf countries - Alqaidoom, Hana Radhi (Kulliyyah of Information and Communication Technology, 2021)
This research is pursued to identify the digital literacy level required to implement Massive Open Online Course (MOOC) by educators in Gulf countries for higher education institutions. It is also intended to determine educators’ acceptance of MOOC in GCC universities. In light of this context, exploring educators’ point of view towards a unified MOOC platform for universities in GCC is also considered as one aspect to highlight in this research. MOOC is adopted by few higher education institutions in the Arab world; however, this kind of learning requires certain level of digital literacy for all stakeholders. This includes most importantly the educators. Eventually, there is a dearth of academic research that study the importance of digital literacy and educators’ acceptance of MOOC in the Gulf countries. Most of the studies focus on the perception and attitude of learners towards MOOC rather than educators. The research answers the questions posited at the beginning which are: What is the current level of digital literacy of educators compared to the digital literacy required to design a MOOC? What is the impact of the demographic variables and other variables on using MOOC in higher education? How does MOOC improve the level of achievement of graduates from the perspectives of educators?. This research has utilized “Digital Literacy Scale” (DLS) to measure the level of digital literacy of educators. While “Unified Theory of Acceptance and Use of Technology” (UTAUT) model has been modified to identify the acceptance of educators of MOOC. To achieve this aim, a mixed methodology is used to gather information about educators and MOOC. A questionnaire survey was administered on a sample size of 200 educators who deliver courses on the most prominent MOOC platforms. The selected platforms are Coursera, EdX, Udacity, FutureLearn, Rwaq and Edraak. Additionally, observations and interviews have been conducted to answer the five questions, and to test the eight hypotheses of the research. Notwithstanding some caveats, results unveiled that educators who currently teach through MOOC platforms have a good level of digital skills. Generally, the educators have a positive attitude towards MOOC, and they support the proposal of developing a unified MOOC platform for universities in Arab world. Finally, the findings revealed a significant impact of factors such as digital literacy and globalization on the use of MOOC.